Kemampuan Beradaptasi UMKM Digital Kota Palu - Risnawati, Risnawati; Natsir , Syahir; Putu Evvy Rossanty , Niluh; Wirastuti , Wiri; Gosal , Rudy; A. H. Lamusa , Faruq (Literasi Jurnal Pengabdian Masyarakat dan Inovasi, 2022)
After COVID 19 was announced as a global pandemic, businesses suddenly changed everything from work processes, business strategies to the most basic things like interactions. COVID-19 has also changed consumer behavior patterns, everyone will start to get used to online shopping. The digital adaptation of SMEs is needed to deal with the existing conditions. This adaptability will be socialized to SMEs typical of Palu City. The purpose of this service is to provide knowledge about the adaptability of digital SMEs in the city of Palu so that they can adapt to rapidly changing business developments according to market demands. The culinary MSME actors typical of the city of Palu are very enthusiastic about accepting the arrival of the service team, while showing the current conditions faced during the COVID-19 pandemic. Culinary SMEs typical of the city of Palu need assistance in making business decisions. In addition, culinary SMEs typical of the city of Palu also require skill ups or even new skills in order to be able to adapt to business developments that are rapidly changing according to market demands.